Multiple Patterns of Perirenal Fat Invasion Are Associated With a Poorer Prognosis Compared With Isolated Invasion: A Proposal for a Revision of T3aN0M0 TNM Staging System - Wang, Zhixian; Yu, Kai; Zhu, Yunpeng; Feng, Chunxiang; Liu, Chang; Liu, Shiliang; Wang, Jing; Zeng, Xiaoyong (Frontiers in Oncology, 2020)
Objectives: Currently, renal cell carcinoma (RCC) presenting with perisinus fat invasion (PSI) and/or perinephric fat invasion (PFI) is merged as one entity, pathological T3a (pT3a); however, the combination of PFI and PSI (PFI+PSI) may not be associated with equivalent prognosis compared with either PFI or PSI alone (PFI/PSI). Here, we analyzed the prognostic significance of PFI+PSI vs. PFI/PSI in pT3aN0–1M0–1 RCC. Method: We identified 5,290 patients with pT3aN0–1M0–1 RCC, treated by nephrectomy, from the Surveillance, Epidemiology and End Results database, between 2010 and 2016. Cox proportional hazards regression and Fine and Gray competing risks regression were fitted to assess risks of survival outcomes, respectively. 1:1 propensity score method was used to minimize differences in the covariates' distributions. Results: Among all patients, 746 patients (14.1%), 2,569 patients (48.5%) and 1,975 patients (37.3%) experienced PFI+SI, PFI, and PSI, respectively, and 3,952 patients (74.7%) without diseases of lymphnode (N1) and/or distant metastasis (M1). PFI alone compared with PSI alone showed a comparable overall survival (OS) and cancer-special survival (CSS), either PFI or PSI alone experienced a better OS and CSS than PFI+PSI. In patients with pT3aN0M0 RCC, PFI+PSI compared with the PFI/PSI was significantly associated with worse OS with hazard ratio (HR) [95% confidence interval (CI)]: 1.38 [1.12–1.69], p = 0.002 and 1.41 [1.06–1.87], p = 0.017 for unmatched data and matched data, respectively, and higher RCC-special mortality (HR [95%CI]: 1.55 [1.21–1.99], p = 0.001 and 1.70 [1.19–2.43], p = 0.004 for unmatched data and matched data, respectively). However, in pT3aN1/M1 RCC patients, PFI+PSI was not significantly associated with RCC-special mortality (HR [95%CI]: 1.02 [0.85–1.23], p = 0.800 and 0.99 [0.79–1.24], p = 0.920 for unmatched data and matched data, respectively) in comparison with PFI/PSI. In addition, invasion type was not an independent risk factor for patient's prognostication in the pT3a RCC with diseases of N1 and/or M1 (all p > 0.5). Conclusion: Multiple invasion patterns (PFI+PSI) are associated with inferior survival relative to PFI/PSI alone in patients with pT3aN0M0 RCC; however, these effects are masked in patients with metastatic disease. These results warrant consideration in the development of the next edition of the tumor-node-metastasis staging system, to improve risk stratification.